A National Land Policy Review in Kenya: Rangelands and Pastoralists' Perspective - Otieno, Ken P. (International Livestock Research Institute, 2024)
This land policy review was supported by the CGIAR Research Initiative Livestock and Climate and the project Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC). This critical analysis of the National Land Policy 2009 was undertaken on the request of the National Land Commission to inform strategic inputs to the policy review process by pastoralists and other rangeland resource users. The review was undertaken by the Resource Conflict Institute (RECONCILE). This exercise is a deliberate move to ensure effective inclusion and consideration of pastoralists’ voices in the policy review process. Through several stakeholder engagements and technical expert contributions from Kenya, Uganda and Tanzania, this policy position paper presents various perspectives and recommendations on the main thematic areas relevant to pastoralists. The process has also benefited from RECONCILE’s work with pastoralists and pastoralism in the region that spans over two decades.